Folates, folic acid and preconception care – a review. Issue 5 (May 2021) - House, Simon H; Nichols, John AA; Rae, Sarah
Summary: The link between folate deficiency and congenital spina bifida defects was first suggested in the 1960s. Although the prevention of these defects by preconception folic acid supplementation was confirmed in a large multi-centre controlled trial in 1991, its subsequent implementation as health education advice has made very little difference. North America's policy of folic acid fortification of flour and bread has had a beneficial impact. No European country has implemented fortification due to concern over possible adverse effects on older subjects, but a recent review shows these to be largely hypothetical and far outweighed by beneficial effects. Recent research by Menezo et al. has, however, shown that folic acid is ineffective for some women with severe fertility problems including recurrent miscarriage and failed in vitro fertilisation. There is a genetically determined bottleneck (677TT) in their folate metabolism that can be successfully overridden by going straight to the next step in the metabolic pathway and taking 5-methylytetrahydrofolate, as a preconception supplement. Menezo suggests that all women with fertility problems should be tested for 677TT. If fortification of flour and bread is to be implemented in the UK, there should be monitoring for possible adverse effects including the incidence of colorectal cancers and cognitive decline. In conclusion, whilst there are concerns that fortification could have a detrimental effect on these conditions, there is sound evidence that it would have much greater beneficial effects.